Adapalene 0.1%/benzoyl peroxide 2.5% gel reduces the risk of atrophic scar formation in moderate inflammatory acne: a split‐face randomized controlled trial. (7th December 2016) - Dreno, B.; Tan, J.; Rivier, M.; Martel, P.; Bissonnette, R.
Abstract: Background: The efficacy of current topical acne treatments in mitigating the potential for acne scarring is not known. Objective: To evaluate the effect of adapalene 0.1%/benzoyl peroxide 2.5% (A/BPO) gel compared to vehicle in reducing the risk of acne scarring. Methods: Multicentre, randomized, investigator‐blinded, vehicle‐controlled, split‐face study conducted over 6 months. Subjects were adults with active moderate facial acne vulgaris and at least 10 atrophic acne scars at baseline. Efficacy evaluations included counts of atrophic acne scars and primary acne lesions as well as a Scar Global Assessment (SGA; 5‐point scale). Results: After 6 months treatment, scar counts remained stable with A/BPO while increasing by approximately 25% with vehicle (mean scar count 11.58 vs. 13.55, respectively, at Month 6; P = 0.036). The percentage of subjects with a SGA of 'almost clear' (hardly visible scars) increased from 9.7% to 45.2% with A/BPO, whereas it did not change with vehicle ( P = 0.0032). Total acne lesion counts decreased by 65% with A/BPO and 36% with vehicle (mean lesion count 8.5 vs. 16.1, respectively, at Month 6; P < 0.001). Limitations: Relatively small study group (31 subjects). Conclusion: Topical long‐term treatment with A/BPO is effective in reducing the risk of atrophic scars and improving the global severity of scarring.